Structural Analysis of Subsurface Based on Shear Wave Velocity Ground Profile Using Ellipticity curve Method in Kendari City Area - Arisona, Arisona (Jurnal Lingkungan dan Bencana Geologi, 2024)
The Research has been done on the analysis of subsurface structures based on ground profiles of shear wave velocity with the ellipticity curve method in the Kendari City area. This research aims to determine the value of shear wave velocity and subsurface structures based on ground profiles of shear wave velocity with the ellipticity curve method and the relationship between the potential levels of damage that occur in the Kendari City area. The microtremor measurement data used consisted of 30 points with a distance of ±1 km between points. The microtremor data were analyzed using Geopsy software with the HVSR method to get the amplification factor value and dominant frequency value at each measurement point. The data from the HVSR method is inverted using the Dinver subsoftware with the ellipticity curve method so that the modeling of ground profiles is obtained which states the value of the shear wave velocity (vs) which is used to determine the subsurface conditions. The results showed that the magnitude of the shear wave velocity (vs) in the Kendari City area varied between 150 m/s - 1300 m/s at a depth of 100 m. The subsurface structure based on ground profiles of shear wave velocity using the ellipticity curve method in the study area consisted of soft soil types at a depth ranging from 1-10 m, moderate soil types found at a depth of 1-20 m, hard soil types (soft rock) found at a depth of 20 – 90 m and rock types are found at depths above 90 m at almost every measurement point. It is suspected that the subsurface conditions in the study area have the potential for shocks and a high level of damage to buildings in the event of an earthquake because they are dominated by thick soft soil material.